Mandibular Full-Arch Rehabilitation over 3 Straight Immediately Loaded Implants: 8 Years of Follow-Up - Márcio de Carvalho Formiga; Magda Nagasawa; Jamil Awad Shibli (Case Reports in Dentistry)
Mandibular full-arch restoration is a good and successful treatment option for totally edentulous patients. In the past years, several studies have described the placement of 4 to 6 implants to restore this type of case; however, an option using 3 dental implants placed in strategic and specific positions could also be an alternative. Therefore, this case report describes a full-arch rehabilitation on 3 straight, immediately loaded implants after 8 years of follow-up. The restoration presented no biological or technical complications during this follow-up period, showing that an adequate treatment plan was able to allow good results using this treatment option.